STRATEGI GURU MENSTIMULASI KEMAMPUAN BERPIKIR KRITIS ANAK USIA TODDLER DI TPA CAHYA MENTARI - Lahagu, Liberat Listina; Nufitriani Kartika Dewi; Swantyka Ilham Prahesti; Himmah Taulany (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Critical thinking is a fundamental competency for young children in meeting the demands of twenty-first-century learning, yet its stimulation among toddlers (2–3 years old) remains far less studied than among kindergarten-age children. Preliminary observation at Cahya Mentari Daycare, Ngudi Waluyo Labschool, revealed that some 2–3-year-old children tend to refuse exploratory activities, such as planting mung beans, before actually attempting them, indicating limited self-confidence and courage to solve problems independently. This study aims to identify indicators of children's critical thinking, describe teachers' strategies for stimulating it, uncover the challenges teachers face, and analyze the efforts made to overcome those challenges. A descriptive qualitative approach was employed, with the classroom teacher as the primary informant and caregivers and the institution's manager as supporting informants. Data were collected through in-depth interviews, participatory observation, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña, comprising data reduction, data display, and conclusion drawing, with credibility established through source and method triangulation. The results show that indicators of children's critical thinking are reflected in two-way communication, an emerging understanding of simple cause-and-effect relationships, and participation in discussion. Teachers stimulated these abilities through guiding questions, a comfortable learning atmosphere, and learning methods such as center-based learning, Project Based Learning, and loose-parts media. The main challenge, low self-confidence among children, was addressed through sustained motivation and gradual scaffolding. These findings underscore the importance of the teacher's role as facilitator in building the foundation of critical thinking from the toddler years onward.